Assessment of Human Resource Management Functions at RSUD Datu Sanggul - Jefry Sondang Kembaren; Ronny Samsul Bahri (Al-Makki Publisher, 2024)
The public sector, particularly hospitals, plays a crucial role in the provision of quality health services. However, many hospitals, including RSUD Datu Sanggul, face challenges in human resource management (HRM) that result in service performance. This study aims to analyze the functions of human resource management (HRM) in the Regional General Hospital (RSUD) Datu Sanggul and its impact on service performance, especially in the Surgical Poly. The method used is a qualitative approach with an exploratory design. Data were collected through observation, questionnaires, and documentation studies, involving 14 hospital leaders as respondents. The results showed that the recruitment and selection process of medical personnel at RSUD Datu Sanggul was still less than optimal, with several inequities and competency mismatches. The implementation of training and development programs for medical personnel recorded activities, but the evaluation of the results was minimal, indicating a lack of impact on performance improvement. In addition, performance appraisal systems and compensation policies also need to be improved to attract and retain medical personnel. This study provides recommendations to improve transparency and standards in the recruitment process, training evaluation, and compensation policy adjustments in order to improve the quality of health services at RSUD Datu Sanggul